Investigations of the dynamics of soil humus utilizing carbon dating techniques - Rennie, D. A., author; Campbell, C. A., author; Paul, Eldor A., author; McCallum, K. J., author; Pub. House of the Academy of the Socialist Republic of Romania, publisher (Colorado State University. Libraries, 1964)
The radioactivity of naturally occurring C14 in soil humus when compared to the C14 activity of a standard of recent origin (carbon dating) can be used to estimate the mean residence time of the soil humus in studying problems in soil genesis, fertility and biochemistry. The apparent mean residence time of humus from a Black Chernozemic soil was approximately 1,000 years. The C14 activity of "Humin" and "Humic Acids" isolated from this soil was lower than that obtained from the whole soil. The fulvic acids, however, had a substantially higher activity and a corresponding lower mean residence time. A Grey Wooded Podzolic soil sample, developed under different vegetation than the chernozemic, had mean residence time approximately 1/3 that of the chernozemic soil. Carbon dating techniques can also be used to study the dynamics of soil organic matter under differing cultural techniques and in soil biochemistry investigations. When integrating these data, factors such as isotopic discrimination and variations in the C14 content of the atmosphere must however be taken into consideration in all studies using this technique.
Summary in English, French and German.
Keywords: turnover rates; dynamics; soil humic compounds; soil organic matter